2022
DOI: 10.3390/ani12101312
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Piglet Temperature Changes: Effect of Intraperitoneal Warm Saline Injection

Abstract: Piglets are poor at thermoregulation immediately following birth and take up to 24 h to recover from their initial temperature drop. The present study aimed to determine if providing piglets with a 15 mL intraperitoneal injection of warm (45 °C) saline at birth would improve their internal temperature recovery to 24 h of age, and how the treatment interacted with birth weight (BWC = 1; ≤0.80 kg, BWC = 2; 0.81 kg to 1.10 kg, and BWC = 3; >1.10 kg), rectal temperature at 1.5 h (RC = 1; ≤32.0 °C, RC = 2; 32.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These findings indicate that, in common with temperate countries, a low birth weight and low rectal temperature at 24 h are potential risk factors that compromise piglet survival during the lactation period in tropical conditions. Interestingly, it was recently demonstrated that a 15 ml intraperitoneal injection of 46°C saline markedly increased the colostrum intake and survival of low birth weight piglets (Tucker et al, 2022).…”
Section: Gestation and Lactation Managementmentioning
confidence: 99%
“…These findings indicate that, in common with temperate countries, a low birth weight and low rectal temperature at 24 h are potential risk factors that compromise piglet survival during the lactation period in tropical conditions. Interestingly, it was recently demonstrated that a 15 ml intraperitoneal injection of 46°C saline markedly increased the colostrum intake and survival of low birth weight piglets (Tucker et al, 2022).…”
Section: Gestation and Lactation Managementmentioning
confidence: 99%
“…Farrowing house ambient temperatures are invariably below the lower critical temperature of piglets, and so piglets must rely on the use of supplemental heat sources or interventions to assist in regulating their temperature. Previous studies have tested a variety of interventions with varying effects on temperature change and subsequent survival, such as energy supplements, drying, and warm intraperitoneal saline injections [2,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%